2015
DOI: 10.1177/1078345815587001
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation and Behavior in Youth in the Juvenile Justice System

Abstract: Suicide is prevalent among youth, especially those involved in the juvenile justice system. Although many studies have examined suicidal ideation and behavior in delinquent youth, prevalence rates vary widely. This paper reviews studies of suicidal ideation and behavior in youth in the juvenile justice system, focusing on the point of contact: incarceration status and stage of judicial processing. Suicidal ideation and behavior are prevalent, and increase with greater involvement in the juvenile justice system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
0
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 63 publications
9
45
0
14
Order By: Relevance
“…A report commissioned by OJJDP noted that correctional conditions frequently fail to meet several best practice guidelines (Sedlak & McPherson 2010). Other studies point to the deleterious consequences of adolescent incarceration on a range of health, education, and economic outcomes (Dierkhising, Lane, Natsuaki 2014; Holman, & Ziedenberg 2006; Stokes, McCoy, Abram, Byck, & Teplin 2015; Teplin, Welty, Abram, Dulcan & Washburn 2012). …”
Section: Introductionmentioning
confidence: 99%
“…A report commissioned by OJJDP noted that correctional conditions frequently fail to meet several best practice guidelines (Sedlak & McPherson 2010). Other studies point to the deleterious consequences of adolescent incarceration on a range of health, education, and economic outcomes (Dierkhising, Lane, Natsuaki 2014; Holman, & Ziedenberg 2006; Stokes, McCoy, Abram, Byck, & Teplin 2015; Teplin, Welty, Abram, Dulcan & Washburn 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Cette divergence entre ce qui est autorévélé par les questionnaires et ce qui est discuté en entrevue face à face semble révéler une difficulté éprouvée par les jeunes contrevenants lorsqu'ils perçoivent devoir exposer leur vulnérabilité. Alors que le lien entre les abus sexuels et physiques vécus et les comportements suicidaires a été démontré auparavant (Bhatta et al, 2014 ;Croysdale et al, 2008 ;Evans et al, 2004 ;Gretton et Clift, 2011 ;Hayes, 2009 ;Kenny et al, 2008 ;Laurier, 2008 ; National Action Alliance for Suicide Prevention : Youth in Contact with the Juvenile Justice System Task Force, 2013 ; Sedlak et McPherson, 2010 ;Stokes et al, 2015), le lien entre les abus émotionnels et les comportements suicidaires est resté, jusqu'à maintenant, peu étudié. Dans le cadre de la présente étude, les résultats dégagés sur la base du MINI portent à croire que l'expérience d'abus émotionnels s'avère un élément important dans la compréhension du risque suicidaire, tout comme les expériences d'abus sexuels.…”
Section: Discussionunclassified
“…Une recension des études portant sur les adolescents et les facteurs de risque de suicide indique en outre que ces trois troubles y sont fortement associés (Evans, Hawton et Rodham, 2004). En ce qui a trait aux événements stressants durant l'enfance, les abus sexuels et physiques sont reconnus comme des facteurs de risque suicidaire chez les jeunes contrevenants (Bhatta et al, 2014 ;Croysdale, Drerup, Bewsey et Hoffmann, 2008 ;Evans et al, 2004 ;Gretton et Clift, 2011 ;Hayes, 2009 ;Kenny et al, 2008 ;Laurier, 2008 ;Laurier et Chagnon, 2011b ; National Action Alliance for Suicide Prevention : Youth in Contact with the Juvenile Justice System Task Force, 2013 ; Sedlak et McPherson, 2010 ;Stokes, McCoy, Abram, Byck et Teplin, 2015). Bien que moins documentés, les abus de nature émotionnelle, telles les remarques et les attaques verbales discréditant le sentiment de valeur personnelle de l'enfant ou son bien-être, ou encore les remarques humiliantes d'un adulte envers l'enfant (Bernstein et Fink, 1998), s'avèrent également liés au risque de suicide (Croysdale et al, 2008).…”
Section: Introductionunclassified
“…In their review, Stokes et al (2015) found depression to be a predictor of suicidal ideation and suicidal behavior and in their meta-analysis of the MAYSI-2, Vincent et al (2008) found females significantly more likely than males to score above the caution cutoff on the Depression-Anxious and Suicide Ideation Scales. Although females, both involved in the juvenile justice system and those in the general population, have higher prevalence rates of suicidal ideation and behavior; males have the highest rates of completed suicide (Stokes et al, 2015).…”
Section: Gender Differencesmentioning
confidence: 99%